2020
DOI: 10.3390/ijms21113914
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Scale Study: First Demonstration of Hydrophobic Membranes for the Removal of Ammonia Molecules from Rendering Condensate Wastewater

Abstract: Hydrophobic membrane contactors represent a promising solution to the problem of recycling ammoniacal nitrogen (N-NH4) molecules from waste, water or wastewater resources. The process has been shown to work best with wastewater streams that present high N-NH4 concentrations, low buffering capacities and low total suspended solids. The removal of N-NH4 from rendering condensate, produced during heat treatment of waste animal tissue, was assessed in this research using a hydrophobic membrane contactor. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…However, this method is only capable of producing a NH 3 fertiliser, whereas the use of membrane distillation allows for the production of (NH 4 ) 2 SO 4 . Hydrophobic membranes have become increasingly popular for extracting NH 3 from WW streams [23,43]. One of the major benefits of using membranes to treat NH 3 in WW is the production of an NH 4 salt (most commonly (NH 4 ) 2 SO 4 ) as a by-product [44].…”
Section: Identification Of Viable By-products From Rendering Condensatementioning
confidence: 99%
See 2 more Smart Citations
“…However, this method is only capable of producing a NH 3 fertiliser, whereas the use of membrane distillation allows for the production of (NH 4 ) 2 SO 4 . Hydrophobic membranes have become increasingly popular for extracting NH 3 from WW streams [23,43]. One of the major benefits of using membranes to treat NH 3 in WW is the production of an NH 4 salt (most commonly (NH 4 ) 2 SO 4 ) as a by-product [44].…”
Section: Identification Of Viable By-products From Rendering Condensatementioning
confidence: 99%
“…The high levels of NH 3 present in RCWW makes it an ideal matrix to produce (NH 4 ) 2 SO 4 fertilizer. A study by Brennan et al [23] stated that the operation costs to produce 1 kg of (NH 4 ) 2 SO 4 was €2.48 and could be sold for €1.54. It was calculated that the present RCWW produces an average of 4.7 million kg of NH 3 a year, which would allow for the production of up to 711,866 kg of 30% (NH 4 ) 2 SO 4 , equating to 1.1 million euro in revenue.…”
Section: Identification Of Viable By-products From Rendering Condensatementioning
confidence: 99%
See 1 more Smart Citation
“…There are publications aimed at the preparation and study of novel artificial membranes [ 5 , 6 , 7 , 8 , 9 , 10 ]. M. Mofasserul Alam et al [ 5 ] prepared and studied a novel anion-exchange membrane designed to separate bisulfite anion from mixt solutions.…”
mentioning
confidence: 99%
“…It was found that the main cause of improving membrane behavior after the surface modification is electroconvection. The effect of the nature of hydrophobic material on the operation parameters of membrane contactors used to remove ammoniacal nitrogen (N-NH 4 ) molecules from wastewater was studied by B. Brennan et al [ 9 ]. It was found that polypropylene membranes are incompatible with the condensate waste, while the polytetrafluoroethylene membranes showed high performance in removing up to 64% of NH 3 molecules from the condensate waste.…”
mentioning
confidence: 99%